Antiretroviral therapy administration reduces neuroinflammation without restoring brain-derived neurotrophic factor signaling in alcohol-administered simian immunodeficiency virus-infected macaques. (15th July 2021) - Maxi, John K.; Foret, Brittany L.; Amedee, Angela M.; McDaniel, Lee S.; Nelson, Steve; Simon, Liz; Edwards, Scott; Molina, Patricia E.
Abstract : Objective: The present study examined interactions between simian immunodeficiency virus (SIV), chronic binge alcohol (CBA), and antiretroviral therapy (ART) on growth factor signaling, neuroinflammatory markers, viral loads (VL), and CD4 + cell counts. Design: Adult male rhesus macaques were administered CBA (13–14 g ethanol (EtOH)/kg per week) or sucrose (SUC) 3 months prior to SIVmac251 infection until the study endpoint. At viral setpoint, a subset of CBA/SIV+ and SUC/SIV+ macaques were randomized to receive daily ART (9-[2-Phosphonyl-methoxypropyly]adenine [PMPA] 20 mg/kg, 2', 3'-dideoxy-5-fluoro-3'-thiacytidine (FTC), 30 mg/kg). Frontal cortex (FC) and basal ganglia (BG) were collected for gene and protein expression. Methods: Relationships between brain and plasma VL or CD4 + cell counts were determined using linear regression. Effects of SIV, CBA, and ART on markers of neuroinflammation and brain-derived neurotrophic factor (BDNF) signaling were determined by ANOVA and linear regression. Results: SIV increased FC and BG neuroinflammatory and glial cell gene expression ( CX3CR1, B2M ), and reduced FC protein kinase B phosphorylation. CBA decreased FC and BG tropomyosin receptor kinase B (TrkB) phosphorylation, and increased full-length TrkB (TrkB-FL) and SLC1A3 expression in FC and BG, respectively. ART suppressed plasma and brain VL, reduced neuroinflammatory gene expression in FC ( IBA1, CX3CR1, and GFAP ), and BG ( CD74 and CD11ß ), and did not restore FC or BG BDNF signaling deficits. Conclusions: Results show ART-mediated reduction in VL and neuroinflammatory gene expression, irrespective of CBA administration. ART did not attenuate SIV- and CBA-mediated BDNF signaling deficits, suggesting these deficits, despite effective neuroinflammation suppression, may explain CBA- and SIV-associated neurocognitive deficits. Therapeutics targeting growth factor signaling may be important adjuvants in treating HIV-associated neurocognitive decline. Abstract : Supplemental Digital Content is available in the text